Pengembangan Media Pembelajaran Komik Digital Materi Persatuan dan Kesatuan pada Siswa Kelas 5 di SDN Pakis V Surabaya - Anggraini, Dwi Nadila; Yuanta, Friendha; Pratiwi, Desi Eka (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the feasibility and effectiveness of digital comic learning media on the material of unity and integrity that can be applied to fifth-grade students at SDN Pakis V Surabaya. This study is a research with Research and Development (R&D) methods, using the ADDIE development model which consists of five stages. These stages include: analysis stage, design stage, development stage, implementation stage, and evaluation stage. The instruments used in this research include questionnaires and tests. The questionnaires are intended for media experts, material experts, and student responses. The tests consist of pretest assessment sheets and posttest assessment sheets. The trial subjects in this research amount to 29 fifth-grade students of SDN Pakis V Surabaya. The validation results by media experts on the digital comic learning media for the material of unity and oneness obtained a score percentage of 98% with the criterion of 'Very Good.' The validation results by content experts obtained a score percentage of 96% with the criterion of 'Very Good.' Meanwhile, the results of student response assessment obtained a score percentage of 98.43% with the criterion of 'Very Good.' Based on the percentage scores obtained, the media is declared suitable for use. Furthermore, the assessment of student learning outcomes (pretest and posttest) obtained a calculated r of 0.974, which is greater than the table r of 0.367, thus the media is declared effective for use.